Accelerated launch of video visits in ambulatory neurology during COVID-19: Key lessons from the Stanford experience. (18th August 2020) - Yang, Laurice; Brown-Johnson, Cati G.; Miller-Kuhlmann, Rebecca; Kling, Samantha M.R.; Saliba-Gustafsson, Erika A.; Shaw, Jonathan G.; Gold, Carl A.; Winget, Marcy
Abstract : The SARS-CoV-2 (COVID-19) pandemic has rapidly moved telemedicine from discretionary to necessary. Here, we describe how the Stanford Neurology Department (1) rapidly adapted to the COVID-19 pandemic, resulting in over 1, 000 video visits within 4 weeks, and (2) accelerated an existing quality improvement plan of a tiered roll out of video visits for ambulatory neurology to a full-scale roll out. Key issues we encountered and addressed were related to equipment/software, provider engagement, workflow/triage, and training. On reflection, the key drivers of our success were provider engagement and dedicated support from a physician champion, who plays a critical role understanding stakeholder needs. Before COVID-19, physician interest in telemedicine was mixed. However, in response to county and state stay-at-home orders related to COVID-19, physician engagement changed completely; all providers wanted to convert a majority of visits to video visits as quickly as possible. Rapid deployment of neurology video visits across all its subspecialties is feasible. Our experience and lessons learned can facilitate broader utilization, acceptance, and normalization of video visits for neurology patients in the present as well as the much anticipated postpandemic era.